Participation of the Polish Episcopal Conference in the Political Discourse of the Third Republic of Poland and the Autonomy and Independence of the State and the Church. Analysis of Selected Positions of the Structural Units of Pec From 2015–2023 - Stępień, Jakub (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The voice of the Catholic Church remains audible in the public debate in the Third Republic of Poland, in every aspect of social life, including political discourse, regarding specific, current activities of representatives of secular authorities in the creation of state policy. From the point of view of the hierarchical and competence structure of the church community, the communications of the structural units of the Polish Episcopal Conference – which in public perception are identified as the official positions of the institutional Church – are of extraordinary importance in this aspect of the functioning of the state community. However, the relevant provisions of secular and church law provide for specific rules for the functioning of the religious community in relation to and with the state, the basis of which is respect for the mutual autonomy and separation of communities. The practice of this type of activity, however, indicates the existence of certain tendencies and phenomena related to the way of formulating this type of messages, which may often constitute a violation of the above-mentioned principle.